Pengaruh Torsi terhadap Kekuatan Longitudinal pada Kapal Peti Kemas - Suci, Indah Melati; Alie, Muhammad Zubair Muis (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
The large deck openings of ultra-large container ships greatly reduce their torsional stiffness, and hydroelastic analysis is a must for reliable structural design. In the initial design stage, the beam model is a rational choice. This study aims to investigate torsion's effect on container ships' strength using a numerical approach based on fatigue boundary conditions and ultimate boundary conditions in the midship region. Regarding fatigue boundary conditions, the dimensional influence of the container ship is obtained at the connection between the longitudinal side shell stiffeners and the transverse web frame for nine structural details, which refer to different arrangements of reinforcing elements. The structural influence on the local stress distribution was assessed along the longitudinal plates between the regular stiffeners bounding the perimeter of the torsion box by calculating the hull girder stresses. Keywords: Container Ships, Cross Section, Torsion, Longitudinal Strength